Situation Report: Romania, 26 January 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Commentary on President Nixon's Message More on the New Bill on Economic Contracts Research Center for Youth Affairs to Expand Activity Lumea on the Role of the Opposition in the Bundestag Deputy Foreign Minister to Scandinavia General Assemblies of Agricultural Production Co-Operatives Miscellaneous